Outcome of instrumented lumbar fusion for low grade spondylolisthesis; Evaluation of interbody fusion with & without cages - Fathy, Mostafa (Medknow Publications & Media Pvt Ltd, 2010)
OBJECT: The aim is to evalute the outcome of posterior lumbar interbody fusion with autologous bone graft versus titanium Cages, BAK system (Bagby – Kuslich, Spine Tech, Inc. Minneapolis, MN) for low grade spondyloisthesis (Grade1,11). Interbody cages have been developed to replace tricortical Interbody grafts in posterior lumbar interbody fusion (PLIF) procedures. The cages provide immediate post operative stability and facilitate bony union with cancellous bone packed in the cage itself. METHOD: We Evaluated 50 consecutive patients in whom surgery was performed between June 2000 to June 2003 in the Main Alexandria University Hospital at EGYPT. Twenty five patients were operated using autologous bone graft and 25 patients using the BAK cages. The neuro–radiologic al work up consisted of; plain X – ray lumbosacral spine including dynamic films preoperative and postoperative follow up; C.T lumbosacral spine and MRI lumbosacral spine. The surgery was performed at L4-5 level in 34 cases and at L5-S1 level in 16 cases. The median follow up was 15 months. RESULTS: Satisfactory fusion was obtained at all levels at a minimum one year follow – up. The fusion rate was 96% (24 patients) for the cage group and 80% (20 patients) for bone graft group however clinical improvement was 64% (16 patients) for those with bone graft group. CONCLUSION: A higher fusion rates and a better clinical outcome have been obtained by Instrumented PLIF with titanium cages that with bone graft. Inderbody fusion cages help to stabilize spainal segment primarily by distracting them as well as by allowing bone ingrowth and fusion. The procedure is safe and effective with 96% fusion rate and 76% overall Satisfactory rate. The use of cages help to distract the space between the vertebral bodies making the correction of the degree of spondylolisthesis easier. Long term follow up revealed better fusion rate and better realignment and less resorption with cages than with bone grafts.